2013
DOI: 10.1287/mnsc.1120.1680
|View full text |Cite
|
Sign up to set email alerts
|

Customer-Driven Misconduct: How Competition Corrupts Business Practices

Abstract: C ompetition among firms yields many benefits but can also encourage firms to engage in corrupt or unethical activities. We argue that competition can lead organizations to provide services that customers demand but that violate government regulations, especially when price competition is restricted. Using 28 million vehicle emissions tests from more than 11,000 facilities, we show that increased competition is associated with greater inspection leniency, a service quality attribute that customers value but is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
56
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 159 publications
(67 citation statements)
references
References 80 publications
(97 reference statements)
6
56
0
Order By: Relevance
“…7 If there were any exogenous variables in any of the two equations, then those variables should be in the regression as well. 8 Another example of having a discontinuity in the data is Bennett et al (2013). The authors exploit changes in the testing protocols for car emissions and find a discontinuity in the passing rate based on the cars' model year.…”
Section: Endnotesmentioning
confidence: 99%
“…7 If there were any exogenous variables in any of the two equations, then those variables should be in the regression as well. 8 Another example of having a discontinuity in the data is Bennett et al (2013). The authors exploit changes in the testing protocols for car emissions and find a discontinuity in the passing rate based on the cars' model year.…”
Section: Endnotesmentioning
confidence: 99%
“…The limited number of studies of the heterogeneity across inspectors' propensity to report violations has identified the importance of their tenure, training, gender, and former exposure to the establishment (Macher, Mayo, and Nickerson 2011, Short, Toffel, and Hugill 2016, Ball, Siemsen, and Shah 2017. Inspector scrutiny among third-party inspection firms has been shown to be influenced by (a) whether it is the inspected establishment or another party that hires the inspection firm and pays for the inspection (Ronen 2010, Duflo et al 2013, Short andToffel 2016), (b) the level of competition among inspection firms (Bennett et al 2013), and (c) whether the inspecting firm has cross-selling opportunities (Koh, Rajgopal, andSrinivasan 2013, Pierce and. In contrast to these demographic aspects of individual inspectors and structural dimensions of the relationship between the inspection firm and the inspected establishment, we explore a very different potential source of inspection bias: where the inspection falls within an inspector's schedule.…”
Section: Inspection Accuracymentioning
confidence: 99%
“…Because inspectors need evidence to justify citing violations (and thus can only cite violations if they are truly present), studies of inspection bias (e.g., Bennett et al 2013, Duflo et al 2013, Short, Toffel, and Hugill 2016 are based on the assumption that deviations from the true number of violations are only due to underdetection, and that bias does not lead inspectors to cite violations that are not actually present. This assumption was validated in our interviews with inspectors, and underlies our empirical approach.…”
Section: Empirical Context: Food Safety Inspectionsmentioning
confidence: 99%
“…Intuitively, for a given level of market-wide misconduct, customers will buy at a higher rate from exclusive experts because they receive a higher expected payo §. The upward sloping line, s (b) !1 ; is the inverse of 4 Although a full discussion of why brand premia persist over time is beyond the scope of the current paper, consumers purchase life insurance and annuities very infrequently and, therefore, have limited opportunities to accumulate knowledge about speciÖc products or update their beliefs about Örmsí reputations. 5 In the insurance market, exclusive agents may o §er multi-product discounts, online account access, 1-800 telephone support, or multiple service locations.…”
Section: Consumersí Buy Ratesmentioning
confidence: 99%
“…Bennett et al (2013) Önd that increased competition also leads to more lenient emissions testing. Levitt and Syverson (2008) Önd that real estate agents invest more e §ort and secure higher prices for their own properties, relative to their customersí homes.…”
mentioning
confidence: 99%